Predictors for sentinel lymph node metastasis of cutaneous melanoma (Revista Argentina de Cirugía, 2021)
Background: multiple risk factors have been described in order to predict sentinel lymph node (SLN) compromise in patients with cutaneous melanoma. However, there is no agreement as to the importance of each of those factors. The aim of this study was to identify risk factors of SLN metastasis. Methods: consecutive SLN biopsies in patients with cutaneous melanoma in the period 2001-2013 were included. Demographic factors and primary tumor characteristics were evaluated and univariate and multivariate analyses were performed.Results: of 117 SLN biopsies, 25 patients (21.3%) had a positive SLN. Age and tumor location were not associated with risk of lymphatic metastasis. Patients with Breslow thickness 1-4 mm were associated  with more nodal involvement than those with thickness < 1mm and those with > 4mm had even higher rate of positive SLN. Ulceration and nodular histology showed higher SLN compromise. Tumor regression and number of mitoses were not associated with positive SLN. In the multivariate analysis Breslow thickness > 4mm and nodular histologic type showed statistical significance.Conclusions: ulceration, Breslow thickness and nodular histologic type are associated with the SLN status. Furthermore, Breslow thickness and nodular histologic type could be independent predictor factors of SLN involvement.
Keywords: cutaneous melanoma; sentinel lymph node biopsy; risk factor